LATIS: A Sample of IGM-selected Protoclusters and Protogroups at z ∼ 2.5 - Andrew B. Newman; Mahdi Qezlou; Gwen C. Rudie; Nima Chartab; Guillermo A. Blanc; Daniel D. Kelson; Simeon Bird; Caitlin Casey; Enrico Congiu; Olga Cucciati; Denise Hung; Brian C. Lemaux; et al. (The Astrophysical Journal)
The Ly α Tomography IMACS Survey (LATIS) has produced large 3D maps of the intergalactic medium (IGM), providing a new window on the cosmic web at z ∼ 2.5. A key advantage of Ly α tomography is that it enables the discovery of overdense regions without the need to detect their galaxy members in spectroscopic surveys, circumventing possible selection biases. We use these maps to identify 37 IGM-selected overdensities as regions of strong and spatially coherent Ly α absorption. Simulations indicate that 85% of these are protoclusters, defined as the progenitors of z = 0 halos with mass M _desc > 10 ^14 M _⊙ , and that nearly all of the rest are protogroups (10 ^13.5 < M _desc / M _⊙ < 10 ^14 ). We estimate the masses and space densities of the IGM-selected overdensities and show they are in accordance with mock surveys. We investigate the LATIS counterparts of some previously reported protoclusters, including the proto-supercluster Hyperion. We identify a new component of Hyperion beyond its previously known extent. We show that the Ly α transmission of the galaxy density peaks within Hyperion is consistent with a simple physical model (the fluctuating Gunn–Peterson approximation), suggesting that active galactic nucleus feedback or other processes have not affected the large-scale gas ionization within this structure as a whole. The LATIS catalog represents an order-of-magnitude increase in the number of IGM-selected protogroups and protoclusters and will enable new investigations of the connections between galaxies and their large-scale environments at cosmic noon.